2000
DOI: 10.3310/hta4100
|View full text |Cite
|
Sign up to set email alerts
|

Publication and related biases.

Abstract: Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see overleaf). NHS R&D HTA Programme T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produced in the most efficient way for those who use, manage and work in the NHS. Research is undertaken in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
291
3
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(305 citation statements)
references
References 208 publications
(459 reference statements)
4
291
3
7
Order By: Relevance
“…According to point of recurrence time from the date of hepatectomy, recurrences were classified into early (≤2 year) and late (>2 year) recurrences [34]. The prognosis of patients with early recurrent tumors was found to be worse than that of patients with late recurrence [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to point of recurrence time from the date of hepatectomy, recurrences were classified into early (≤2 year) and late (>2 year) recurrences [34]. The prognosis of patients with early recurrent tumors was found to be worse than that of patients with late recurrence [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, potential publication bias might be present, by not including unpublished studies. However, it was demonstrated that the use of unpublished data may not necessarily reduce the bias in meta-analysis [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias has been well recognized in scientiWc publications (Song et al 2000). Results from ecological studies, like those from any other Weld, are preferred by journals and therefore published more easily, if signiWcant treatment eVects were found (Jennions and Moller 2002;Kotiaho and Tomkins 2002;Moller and Jennions 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of individual studies on summary estimate of effect, we performed an influence analysis in which the pooled estimates were recalculated omitting one study at a time. We did not assess publication bias, because each subgroup pooled estimate included fewer than ten trials [17]. Analyses were conducted using Review Manager, version 5.0 (Copenhagen, The Nordic Cochrane Centre, The Cochrane Collaboration, 2008).…”
Section: Methodsmentioning
confidence: 99%